2002
DOI: 10.1097/00006565-200202000-00004
|View full text |Cite
|
Sign up to set email alerts
|

Test characteristics of the urine Gram stain in infants ≤ 60 days of age with fever

Abstract: The Gram stain has excellent test characteristics for the preliminary diagnosis of a UTI in febrile infants. Patient disposition and therapy will likely change if clinical protocols and guidelines use the Gram stain rather than urine microscopy for preliminary diagnosis of UTI in infants.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
34
1
2

Year Published

2005
2005
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(38 citation statements)
references
References 8 publications
1
34
1
2
Order By: Relevance
“…Two of these were also included in our review, 177,178 and one was excluded 179 as it was based on secondary care. The review is therefore not considered further and this synthesis focuses instead on the eight primary studies.…”
Section: Nappy Padsmentioning
confidence: 99%
“…Two of these were also included in our review, 177,178 and one was excluded 179 as it was based on secondary care. The review is therefore not considered further and this synthesis focuses instead on the eight primary studies.…”
Section: Nappy Padsmentioning
confidence: 99%
“…45,47,53,55,59,60,62,70,[72][73][74][75]78,81,84,89,91,101,105,[110][111][112]230 More than half (17/23) of these studies did not include an appropriate spectrum of patients, and patient selection criteria were often inadequately described. Avoidance of test review bias was poorly reported; 14 out of the 23 studies did not report whether those interpreting results were blinded to the results of other tests.…”
Section: Nitritementioning
confidence: 99%
“…The 90.8% sensitivity of laboratoryperformed dipstick in this study is higher than previous estimates of 75% to 85%. 9,16,26,27 However, these other studies defined UTI at a lower threshold of $10 000 CFUs per mL and/or emphasized infants and children older than 90 days.Our study has several limitations. Data analysis was retrospectively performed from a data set collected for other purposes.…”
mentioning
confidence: 99%